Civil Justice: Lay Judges in the EU Countries - Stefan Machura (Oñati Socio-Legal Series)
Lay judges fulfill important functions for the justice system of a country. In the European Union member states, scholars have analysed the use of lay judges in criminal cases. However, little is known about lay participation in civil justice. The paper introduces commonly cited reasons to have lay judges as well as the principal forms of lay participation and then surveys the EU countries for its implementation in civil cases. Mixed tribunals, involving lay judges under the leadership of a professional judge, are relatively frequent. Several countries have special labour courts or commercial courts with lay members and others have single lay judges, or all-lay judge panels. Roughly a third of the 28 EU member states have no lay participation in civil justice but only three of those have no lay judges in any branch of the courts. Almost all the reasons for including lay decision makers are served somehow by the existing forms, including providing different experiences and perhaps expert knowledge. The article concludes, citing non-EU states and lay participation in criminal and administrative courts as further evidence, that lay judges in one form or another are an element of European legal systems.